Remote Work Paradox: Examining the Tension between Workplace Flexibility, Employee Productivity and Organisational Performance - James Oluwapamilerin Obisesan; Abigail Opeyemi Ogunleru; Kolade Ajibola; Olaitan Olaleye (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
The rapid expansion of remote work has transformed conventional employment arrangements, offering employees greater flexibility while simultaneously generating complex challenges for productivity and organisational performance. This study examines the remote work paradox, focusing on the tension between workplace flexibility, employee productivity and organisational performance. The study is premised on the argument that although remote work provides employees with greater autonomy, reduced commuting demands and improved opportunities for work-life integration, these benefits may coexist with challenges relating to work intensification, blurred work-life boundaries, social isolation, communication difficulties, employee monitoring and weakened organisational cohesion. The study adopts a qualitative research approach based exclusively on secondary data obtained from relevant peer-reviewed journal articles, scholarly books, institutional reports and credible industry publications on remote work and organisational behaviour. The data were subjected to thematic analysis to identify recurring patterns and perspectives concerning the relationship between remote work flexibility, employee productivity and organisational outcomes. The analysis reveals that the productivity implications of remote work are not universally positive or negative but are shaped by organisational culture, job characteristics, technological infrastructure, managerial practices, employee autonomy and the nature of collaboration required. While flexibility can enhance employee satisfaction, motivation and individual productivity, excessive autonomy, digital fatigue, isolation and inadequate organisational support may undermine collaboration, innovation and long-term organisational performance. The study concludes that the remote work paradox lies in the coexistence of flexibility and control, autonomy and accountability, as well as individual productivity and collective organisational effectiveness. It recommends that organisations adopt hybrid and context-sensitive remote work policies, strengthen digital communication systems, establish clear performance expectations and prioritise employee well-being to maximise the benefits of remote work while mitigating its unintended consequences.